Zakat Management Instutition: Management and Strategy - Melis, Melis; Choiriyah, Choiriyah; Saprida, Saprida (SALAM: Jurnal Sosial dan Budaya Syar-i, 2020)
The distribution of zakat is based on priority scale by paying attention to the principles of equity, justice and territoriality. In addition to receiving zakat (managing zakat), BAZNAS can receive and distribute donations, alms, and other religious social funds. The distribution and utilization of donations, alms, and other religious social funds are carried out in accordance with Islamic law and are carried out in accordance with the intended purpose of the giver. The management of donations, alms, and other religious social funds must be recorded in a separate bookkeeping. Here the importance of reports by BAZNAS, provincial BAZNAS, and Regency / City BAZNAS which contains the accountability and performance of the management of Zakat, infaq, alms and other religious social funds. ZIS managers are not only BAZNAS but there are also LAZ. This article will describe the management and management strategies of ZIS in detail.Keywords: ZIS, BAZNAS, LAZ AbstrakPendistribusian zakat dilakukan berdasarkan skala prioritas dengan memperhatikan prinsip pemerataan, keadilan, dan ke wilayahan. Selain menerima zakat (mengelola zakat), BAZNAS dapat menerima dan mendistribusikan infak, sedekah, dan dana sosial keagamaan lainnya. Pendistribusian dan pendayagunaan infak, sedekah, dan dana sosial keagamaan lainnya tersebut dilakukan sesuai dengan syariat Islam dan dilakukan sesuai dengan peruntukkan yang diikrarkan oleh pemberi.Pengelolaan infak, sedekah, dan dana sosial keagamaan lainnya harus dicatat dalam pembukuan tersendiri. Disini pentingnya laporan oleh BAZNAS, BAZNAS provinsi, dan BAZNAS Kabupaten/Kota yang memuat akuntabilitas dan kinerja pelaksanaan Pengelolaan Zakat, infak, sedekah, dan dana sosial keagamaan lainnya. Pengelola ZIS tidak hanya BAZNAS tetapi juga ada LAZ. Artikel ini akan memaparkan manajemen dan strategi pengelolaan ZIS secara detail.Kata Kunci: ZIS, BAZNAS, LAZ